1064 Extra-Articular Tibial Deformity Management in Total Knee Replacement. (12th October 2021) - Choi, S M; Kumar, R; Morgan-Jones, R; Agarwal, S
Abstract: Aim: In knee replacements, restoration of mechanical alignment is essential. Patients with extra-articular deformities (EAD) pose challenges in planning knee replacements. We present a method, based on our experience and review of literature on planning knee replacement surgery, in the presence of extra-articular coronal plane deformity of the tibia. Method: Retrospective analysis was made of six patients with EAD of the tibia who underwent knee replacement at our centre. Mechanical axis of the tibia is considered and positioning of the tibia component is planned perpendicular to the mechanical axis of the tibia. The integrity of the collaterals determines the need for correction. Tibial resection >15mm from medial or lateral aspect of the tibia is an indication for corrective osteotomy prior to replacement surgery. The hip knee ankle angle (HKA) was noted. Pre-operative, post-operative clinical score, degree of constraints and post-operative complications were recorded. A post-operative long leg alignment radiograph was obtained. Result: All patients had total knee replacement without correction of deformity. Adequate alignment of the limb and restoration of mechanical axis was achieved in all six patients without the need for correction of tibial deformity. All patients had improvement in their HKA angle and Oxford knee score. No re-operations were required, and no complications recorded. Conclusions: Our study will help provide guidance on operative planning and decisions making for patients with extra-articular coronal plane tibial deformities.